Chronic angiotensin II infusion causes differential responses in regional sympathetic nerve activity in rats - Yoshimoto, Misa (2010)
Angiotensin II (AngII) – induced hypertension in experimental animals has been proposed to be due in part to activation of the sympathetic nervous system. This sympathetic activation appears to be accentuated in animals consuming a high salt diet (AngII-salt hypertension). However, accurate quantification of sympathetic activity is difficult and controversy remains. A particularly important question is: What are the critical vascular beds targeted by increased sympathetic nerve activity (SNA) in AngII-salt hypertension? To address this issue, mean arterial pressure (MAP) and renal (RSNA) or lumbar SNA (LSNA) were continuously recorded during a 5 day control period, 11 days of AngII (150 ng/kg/min, sc) and a 5 day recovery period in conscious rats on a high salt (2% NaCl) diet. Whereas MAP reached a new steady-state level of 30-35 mmHg above control levels by the end of the AngII period, RSNA decreased by 40% during the first 7 days of AngII and then returned towards control levels by day 10 of AngII. In contrast, LSNA remained at control levels throughout the AngII period. In another experiment we measured hindlimb norepinephrine (NE) spillover in conscious rats on normal (0.4%) or high (2.0%) salt diets before and during 14 days of AngII administration. AngII had no significant affect on hindlimb NE spillover in either group. We conclude that chronic AngII modulates renal and lumbar SNA differentially in rats consuming a high salt diet and that AngII-salt hypertension in the rat is not caused by increased SNA to the renal or hindlimb vascular beds.